Low-Dose Radiotherapy Versus Moderate-Dose Radiotherapy for the Treatment of Indolent Orbital Adnexal Lymphomas - Baron, Jonathan; Wright, Christopher M.; Lee, Daniel Y.; Carpenter, Maribel; Manjunath, Shwetha H.; Briceño, César A.; Chong, Elise; Maity, Amit; Plastaras, John P.; Paydar, Ima (Frontiers in Oncology, 2021)
Purpose: Radiation therapy (RT) with doses ranging from 24 Gray (Gy) to 40 Gy is a proven treatment modality for indolent orbital adnexal lymphoma (IOAL), but recently the use of low dose RT (LDRT, defined as 2 Gy x 2 fractions) has become a notable alternative. However, no prior data exists comparing outcomes following LDRT to moderate-dose RT (MDRT, RT dose 4–36 Gy). We present a single institution retrospective analysis comparing outcomes of patients with IOALs following LDRT or MDRT. Methods: A total of 36 patients treated with 38 consecutive courses of RT were identified; LDRT was delivered for 14 courses and MDRT for 24 courses. Overall response rates (ORR) were recorded according to Deauville or RECIST criteria with a response characterized as a complete response (CR) or partial response. Local control (LC), orbital control (OC), and overall survival (OS) rates were estimated with the Kaplan-Meier method. RT toxicity was graded per CTCAEv5 and compared with the Fisher’s exact test. Results: Median follow-up time was 29 months (m) (range, 4-129m), and median MDRT dose used was 24 Gy (range 21-36 Gy). Overall response rates (ORR) were 100% (CR 50%) and 87.5% (CR 58.3%) following LDRT and MDRT, respectively. OS at 2 years was 100% and 95% for the LDRT and MDRT groups, respectively (p=0.36). LC rates at 2 years was 100% for both LDRT and MDRT groups and at 4 years was 100% and 89% for the LDRT and MDRT groups, respectively (p=0.56). The 4-year OC rate (including both ipsilateral and contralateral relapses) was 80% and 85% for the LDRT and MDRT groups, respectively (p=0.79). No patient required treatment with RT to a previously irradiated orbit. Acute toxicities were reported following 6 LDRT courses compared to 20 MDRT courses (p=.014). No Grade 3 or higher acute toxicities occurred in either group. Late toxicities were reported following 2 LDRT courses compared to 10 MDRT courses (p=0.147). Conclusions: LDRT produced similar ORR, LC, OC, and OS rates compared to MDRT with fewer acute and minimal late toxicities reported. Future multi-center studies with larger patient numbers are warranted to show significant associations.